Grazing behaviour of a non‐herbivorous characin: revisiting plasticity. Issue 2 (12th June 2014) - Marques, P. S.; Costa, M. F.; Corrêa, C. C. D.; Marinho, M. M.; Mazzoni, R.
<x xml:space="preserve">Abstract</x> Feeding behaviour and diet of Bryconamericus microcephalus differed between canopy conditions. At the open canopy site, a behavioural modification, grazing on algae, was observed. This was also reflected in gut content analysis and suggests behavioural plasticity in response to resource availability.